Prevalence and clinical features of severe diabetic ketoacidosis treated in pediatric intensive care unit: a 5-year monocentric experience - Stefano Passanisi; Giuseppina Salzano; Pietro Basile; Bruno Bombaci; Flavia Caime; Immacolata Rulli; Mariella Valenzise; Eloisa Gitto; Fortunato Lombardo (BMC, 2023)
Abstract Background Diabetic ketoacidosis (DKA) is one of the most alarming concerns in the management of type 1 diabetes (T1D) in pediatric age. Prevalence of DKA at the onset of diabetes ranges from 30 to 40%. In selected cases of severe DKA, admission to pediatric intensive care unit (PICU) should be considered. Methods This study aims to assess the prevalence of severe DKA treated in PICU in our 5-year monocentric experience. Secondary outcome of the study was to describe the main demographical and clinical features of individuals who required admission to PICU. All clinical data were collected by retrospectively reviewing the electronic medical records of children and adolescents with diabetes hospitalized in our University Hospital from January 2017 to December 2022. Results During the study period, 103 children and adolescents were newly diagnosed with T1D. Among these, 51.5% presented clinical criteria for DKA and almost 10% needed to be treated in PICU. A higher rate of new T1D diagnoses was observed in 2021, as well as episodes of severe DKA being more frequent than in previous years. Due to severe clinical manifestations of DKA, 10 subjects (9.7%) with T1D onset needed to be treated in PICU. Of these, four children were younger than 5. The great majority came from a low household income and some of them had also immigrant background. The most common complication of DKA was acute kidney injury presented by four children. Other complications were cerebral edema, papilledema and acute esophageal necrosis. A 15-year-old girl had deep vein thrombosis (DVT) that evolved into multiple organ failure leading to death. Conclusions Our findings demonstrated that severe DKA is still quite common in children and adolescents at T1D onset, especially in some areas such as Southern Italy. Public awareness campaigns should be increasingly promoted to facilitate the recognition of early symptoms of diabetes and to reduce morbidity and mortality related to DKA.